The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jocn.12766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a hospital‐based education programme on self‐care behaviour, care dependency and quality of life in patients with heart failure – a randomised controlled trial

Abstract: The easy to implement and short educational intervention has a positive effect on self-care behaviour for patients with heart failure. However, there was no effect on quality of life and care dependency. To improve quality of life and to influence care dependency, different measures have to be applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 34 publications
(60 reference statements)
1
63
1
14
Order By: Relevance
“…This study demonstrated that the HETF improved the self‐efficacy of RA patients, even when considering the time cumulative effect and the patients who were lost to follow‐up. Our results were similar to the results of Koberich and Wu (Koberich, Lohrmann, Mittag, & Dassen, ; Wu, Liang, Lee, Yu, & Kao, ). Health education has been widely applied to the learning of knowledge and skills about self‐management.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated that the HETF improved the self‐efficacy of RA patients, even when considering the time cumulative effect and the patients who were lost to follow‐up. Our results were similar to the results of Koberich and Wu (Koberich, Lohrmann, Mittag, & Dassen, ; Wu, Liang, Lee, Yu, & Kao, ). Health education has been widely applied to the learning of knowledge and skills about self‐management.…”
Section: Discussionsupporting
confidence: 92%
“…Aligning with the results from our study, many authors have established the relationship between knowledge deficit and compliance issues (Boyde et al., ; Padilla‐Zárate & Padilla‐Aguirre, ; Piñeiro et al., ; Sánchez‐Gavira et al., ). For example, Koberich, Lohrmann, Mittag, and Dassen () demonstrated that a single educational session preceded by a telephone follow‐up was able to improve the overall self‐care behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with noncommunicable diseases, known as chronic diseases, need continual medical monitoring and nursing care. No significant differences in the degrees of care dependency 3 months after hospital admission were found in the population of interest [24].…”
Section: Care Dependencymentioning
confidence: 73%
“…The CDS was used to measure the levels of care dependency in cases of heart failure [24], which is similar to stroke as a noncommunicable diseases. Patients with noncommunicable diseases, known as chronic diseases, need continual medical monitoring and nursing care.…”
Section: Care Dependencymentioning
confidence: 99%